The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0975-1475.132527
|View full text |Cite
|
Sign up to set email alerts
|

Pulp tissue in sex determination: A fluorescent microscopic study

Abstract: Aims:To determine and compare the reliability of pulp tissue in determination of sex and to analyze whether caries have any effect on fluorescent body test.Materials and Methods:This study was carried on 50 maxillary and mandibular teeth (25 male teeth and 25 female teeth), which were indicated for extraction. The teeth are categorized into 5 groups, 10 each (5 from males and 5 from females) on the basis of caries progression. The pulp cells are stained with quinacrine hydrochloride and observed with fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Seno and Ishizu carried out the detection of Y chromosome in the nuclei of dental pulp. [ 34 ] Their study result was that over 30% of the male pulpal tissue showed positivity for F-bodies. F-bodies could be examined even in teeth as old as 5 months after extraction.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Seno and Ishizu carried out the detection of Y chromosome in the nuclei of dental pulp. [ 34 ] Their study result was that over 30% of the male pulpal tissue showed positivity for F-bodies. F-bodies could be examined even in teeth as old as 5 months after extraction.…”
Section: Molecular Analysismentioning
confidence: 99%